PERANCANGAN APLIKASI PERHITUNGAN IURAN BPJS REMUNERASI RSUD KOTA SALATIGA UNTUK ASN BERBASIS DEKSTOP - Santoso, Alfa Fortunata Moses; Papilaya, Frederick Samuel (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
In the era of increasingly advanced technological development there are many supporting factors in supporting change or innovation from all aspects. The development of a technology really helps human work in various ways. All fields, both government and companies, have used technology in carrying out every service and business process, and technology itself has become an important and needed thing in all these fields. Currently the Salatiga city Diskominfo in collaboration with the Salatiga city hospital is making changes in the process of calculating the BPJS contributions to hospital employees, the old manual process has been changed into a form of a desktop-based application system, because the data input process is still done manually. many employees do not pay the BPJS contributions. Because the Salatiga City Hospital wants to take advantage of technology that is growing and does not require a lot of human resources to run the application. To create a desktop-based application system, a supporting framework is needed, namely the Delphi 10.4 Community Edition framework. This framework is very useful for programmers who will make an application because the template provided is very easy to understand so that programmers can easily make the application. This desktop-based application that was created can later make it easier for admins to manage input output data so that it becomes easier and more efficiently.